MEDICAL HISTORY FORMER SERVICEMEN, WITH ALCOHOL DEPENDENCE - Gaydabrus, A.V. (World of Medicine and Biology, 2013)
Analysis of 104 case histories former servicemen (FS), were treated on alcohol dependence in hospital clinics of psychiatry Military Medical Clinical Centre of the Northern region from 1996 to 2009. The research FS patients who were treated on alcohol at the first time and again the difference in length how long they were in the dismissal. The less time spent in the reserve was in patients with secondary hospitalization, indicating the possibility of developing the disease while in the service. In patients with binge drinking (BD) (80 histories) and patients who have every day of alcoholisation (EDA) (23 patients) were the same length of term of alcoholisation. The patients' age, length of service and the time spent in retirement was greater in patients with EDA, daily alcohol intake greater in patients with BD. Taking this into account, we can conclude that with age increases the risk of EDA.The some difference in the medical history of patients FS and civilian patients. Civilian patients had longer duration of alcohol length and duration of drinking bouts. The vast majority FS had higher military education, while civilian patients mostly had secondary vocational education. Among FS patients with dominated by tobacco abuse, which also affects the occurrence and course of comorbidities. A significant difference in age of patients received education features of the disease, frequency and duration of hospitalization related addictions were compared FS and civilian patients. The obtained data may be considered for the improve primary prevention in the armed forces.
Keywords: former servicemen; alcohol dependence